Theoretical Study Toward Understanding the Electronic Properties of Armchair Hetero Nanotubes - Laith A. Algharagholy (University of Thi-Qar Journal, 2019)
Using the density functional theory ‘DFT’ code ‘SIESTA’ combined with a Green’s function scattering approach ‘GFSA’ code ‘GOLLUM’, we investigate the electronic properties of hetero nanotubes, density of states ‘DOS’, electronic band structure BS, transmission coefficient T(E) and current-voltage curve. We simulated four different hetero structures of nanotubes which are: 1- Hetero nanotube with one graphene ring and one boron nitride ring. 2- Hetero nanotube with two graphene ring and one boron nitride rings. 3- Hetero nanotube with three graphene ring and one boron nitride rings. 4- Hetero nanotube with four graphene ring and one boron nitride rings nanotubes. The results show that there is a clear reduction in energy gap ‘Eg’ of hetero nanotubes comparing with the insulator boron nitride (Eg 4.6 eV) and also this kind of hetero nanotubes have zero states at Fermi energy comparing with conductor carbon nanotube which has finite states at Fermi energy. This is could be a good method to design a semiconductor with desirable band gap.